Influence of Physical and Mechanical Parameters on Cavitation Erosion and Antifouling Behaviour of Multilayer Silica-Based Hybrid Sol–Gel Coatings on Aluminium Alloys - Manasa Hegde; Marta Mroczkowska; Joseph Mohan; Adriana Cunha Neves; Yvonne Kavanagh; Brendan Duffy; Edmond F. Tobin (Eng, 2023)
Sol–gel coatings can provide anti-fouling and erosion resistance while being safe to use in the marine environment. MAPTMS/ZPO multilayer coatings deposited on the AA2024-T3 aluminium surface using the dip-coating method at three different thicknesses (2, 4, and 6 µm) are investigated in this work. The coatings are characterised in terms of physical and mechanical properties, and these properties are investigated in comparison to previously obtained cavitation erosion resistance levels of the coatings. Additionally, the efficiency of the coatings against biofouling was assessed using Phaeodactylum tricornutum, a marine diatom. The influence of the formation of organic–inorganic hybrid materials (OIHMs) from the prepared sols on the physical and mechanical properties of the coatings were analysed. A variety of techniques, including attenuated total reflection Fourier-transform infrared spectroscopy (ATR-FTIR), water contact angle (WCA) measurements, pencil hardness testing, cross-cut adhesion testing, a roughness profilometer, and nano-indentation, were performed on the bare and coated substrates. The results indicated that the thickness, hydrophobicity, and adherence of the coatings are strongly affected by the roughness. The elastic strain failure (H/E) and resistance to plastic deformation (H3/E2) coefficients were higher than those of the bare substrate before and after the cavitation erosion test, indicating that the coating had a higher ability to withstand deformation in comparison to the substrate alone. Furthermore, the microscopic analysis of a marine diatom, Phaeodactylum tricornutum, revealed that coated surfaces exhibited a decreased rate of bacterial adhesion and biofilm formation. The data show that sol–gel formed coatings outperform uncoated AA2024-T3 in terms of hardness, elastic strain, plastic deformation, and biofouling resistance. These characteristics are attributed to the coatings’ mechanical and adhesive capabilities, as well as their tribological behaviour.